2023
DOI: 10.1186/s12903-023-03286-3
|View full text |Cite
|
Sign up to set email alerts
|

Serious game as oral histology learning strategy for undergraduate dental students; crossover randomized controlled trial

Lisa R. Amir,
Irene C. Leonardy,
Salsabila N. Dewatmoko
et al.

Abstract: Background Oral histology is perceived by dental students as a challenging subject and often struggle to recognize the long-term relevance of understanding the cells and tissues at the microscopic level. Serious games have been reported to have a positive effect on student cognitive skills and learning motivation. However, there is still a limited amount of research supporting the effectiveness of serious games as a learning method in dentistry. The present study aimed to evaluate the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In several studies, students have reported that gamification enhances their interest in the course subject, knowledge acquisition, and retention, emphasizing the most critical aspect of the lesson for review [ 20 ]. Similar to the current study, high levels of user satisfaction and perception were reported in other studies using game-based learning for learning orofacial spaces [ 9 ], oral histology [ 6 ], factual knowledge [ 21 ], and clinical communication [ 13 ]. Tantawi et al [ 22 ] reported that gamification significantly improved dental students' academic writing scores; however, their writing satisfaction and self-perceived improvement were modest.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In several studies, students have reported that gamification enhances their interest in the course subject, knowledge acquisition, and retention, emphasizing the most critical aspect of the lesson for review [ 20 ]. Similar to the current study, high levels of user satisfaction and perception were reported in other studies using game-based learning for learning orofacial spaces [ 9 ], oral histology [ 6 ], factual knowledge [ 21 ], and clinical communication [ 13 ]. Tantawi et al [ 22 ] reported that gamification significantly improved dental students' academic writing scores; however, their writing satisfaction and self-perceived improvement were modest.…”
Section: Discussionsupporting
confidence: 87%
“…Gamification incorporates game elements into non-game contexts to increase student motivation and engagement [ 5 ]. Game-based learning has a pedagogical purpose [ 6 ]. In dentistry, the use of online gamification platforms, such as Kahoot!®, has resulted in increased satisfaction among dental students in the teaching of microbiology, immunology, and histology concepts [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation